Arabic Linguistic Creativity in Informal Communication: An Analysis of Non-Standard Expressions and Pragmatic Functions - Aditia, Dimas; Naknawa, Dulyawit; Setiawan, Agus; Muhammad, Eqtada Bilhady (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
Arabic language use in university contexts is often dominated by Standard Arabic (fusha) and emphasizes grammatical accuracy. However, in everyday informal interactions, students frequently employ more flexible, creative, and socially driven forms of expression that diverge from formal norms. This phenomenon reflects the dynamic nature of language as a socio-pragmatic resource shaped by interactional needs and community practices. This study aims to: (1) identify the types of non-standard expressions used in students’ everyday conversations; (2) explain the interactional contexts in which these expressions occur; and (3) analyze the pragmatic functions of non-standard expressions in students’ social relationships, including their roles in building solidarity, conveying emotions, strengthening interpersonal bonds, and sustaining group identity. Using a qualitative descriptive design, data were collected through participant observation and in-depth interviews with purposively selected students who actively engage in informal interaction. Data were analyzed with Miles, Huberman, and Saldaña’s interactive model (data condensation, data display, and conclusion drawing/verification). Trustworthiness was strengthened through source triangulation and member checking. The findings reveal 21 non-standard expressions that are recurrent and mutually intelligible within the student community. These expressions fall into six categories—lexical innovation, expressions uncommon in formal norms, shortening/ellipsis, repetition, cross-linguistic adaptation, and creative forms—and cluster across eight recurring interactional contexts. Pragmatically, they function to build solidarity, express emotions and bodily states, maintain relational harmony (facework), and sustain group identity. Overall, non-standard Arabic use should be viewed as an adaptive socio-pragmatic practice that strengthens pragmatic competence in Arabic language education.